PENGEMBANGAN MODEL SUPERVISI PENDIDIKAN BERBASIS TEKNOLOGI DIGITAL DI SDN 173547 TAMBUNAN - Novalina S. Silaban; Sarjani J.M. Sianturi; Hely Joisen; Kepler Sianturi; Lustani Samosir (STKIP Subang, 2026)
The rapid advancement of digital technology has significantly transformed various aspects of education, including the supervision system in schools. However, the implementation of educational supervision in many elementary schools, including SDN 173547 Tambunan, remains largely conventional and has not optimally utilized digital technology, resulting in less effective monitoring and evaluation of learning processes. This study aims to develop a digital technology-based educational supervision model to improve the effectiveness of supervision and enhance teacher professionalism. The research employs a qualitative descriptive approach with a case study design, involving data collection through interviews, observations, and documentation. The findings indicate that the integration of digital platforms, online supervision, and data-driven analysis can improve the efficiency, flexibility, and objectivity of supervision processes. Furthermore, the use of learning analytics and digital documentation enables school principals to provide faster and more accurate feedback to teachers. The developed model demonstrates that digital-based supervision not only enhances the quality of instructional practices but also fosters continuous professional development among teachers. However, challenges such as limited infrastructure, varying levels of digital competence among teachers, and resistance to change remain critical factors that need to be addressed for successful implementation. Therefore, a comprehensive and adaptive digital supervision model is essential to support sustainable educational quality improvement in elementary schools.